Variability and acceptability in Trinidadian English. Issue 3 (9th April 2020) - Wilson, Guyanne
Abstract: A growing body of work, most of it corpus‐based, looks at variable agreement with collective nouns and in existential constructions in English. However, few studies have looked at these particular features in Caribbean Englishes, and none of these have taken an acceptability approach. In this paper, results of an online survey measuring the acceptability of variable agreement in collective nouns and there + be existential constructions are reported. Additionally, the relationship between the latter forms and the Creole existential it+ have is also considered. Speakers of Trinidadian English are found to hold conservative views towards variation in these contexts. For collective nouns, singular agreement is overwhelmingly preferred, and standard agreement in there + be constructions is also preferred, despite the trend in other Englishes towards the use of non‐standard agreement, particularly with the there's form. Interestingly, the Creole form is judged more favourably than the non‐standard there + be existential forms.